2020
DOI: 10.1053/j.gastro.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Increases Maturation of Brush Borders and SGLT1 Activity in MYO5B-deficient Mice, a Model of Microvillus Inclusion Disease

Abstract: BACKGROUND & AIM: Myosin VB (MYO5B) is an essential trafficking protein for membrane recycling in gastrointestinal epithelial cells. The inactivating mutations of MYO5B cause the congenital diarrheal disease, microvillus inclusion disease (MVID). MYO5B deficiency in mice causes mislocalization of SGLT1 and NHE3, but retained apical function of CFTR, resulting in malabsorption and secretory diarrhea. Activation of lysophosphatidic acid (LPA) receptors can improve diarrhea, but the effect of LPA on MVID symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 52 publications
4
42
0
Order By: Relevance
“…In support of this concept, adult inducible VillinCre ERT2 ;Myo5b floxed/floxed mice show many intestinal alterations after loss of Myo5b including diarrhea, however, they do not have an intestinal barrier defect based on tissue resistance and dextran permeability measurements. 11,12 We observed that in Myo5b KO mice, polarity complex proteins Crumbs3, Patj, Pals1, and aPKC all were present in intracellular inclusions. These findings appear to mirror observations with enteric pathogens.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In support of this concept, adult inducible VillinCre ERT2 ;Myo5b floxed/floxed mice show many intestinal alterations after loss of Myo5b including diarrhea, however, they do not have an intestinal barrier defect based on tissue resistance and dextran permeability measurements. 11,12 We observed that in Myo5b KO mice, polarity complex proteins Crumbs3, Patj, Pals1, and aPKC all were present in intracellular inclusions. These findings appear to mirror observations with enteric pathogens.…”
Section: Discussionmentioning
confidence: 88%
“…[3][4][5][6][7][8][9] MVID is characterized by severe congenital diarrhea, resulting from an inability to properly absorb water coupled with active chloride secretion, which drives further dehydration. [10][11][12][13][14] The presence of intracellular inclusions containing microvilli is a hallmark of MVID. 6,15 We previously showed that inclusions in Myo5b-deficient enterocytes form through apical bulk endocytosis, which requires Pacsin2 and Dynamin2.…”
mentioning
confidence: 99%
“…MVID enterocytes regularly display conspicuous lysosomes and other large compartments that partially contain still identifiable subcellular compounds and apical marker proteins, including apical sodium transporters sodium/glucose cotransporter 1 (SGLT1) and NHE3, for example [ 68 ]. According to morphological criteria those latter compartments have been tentatively classified as autophagosomes and autophagolysosomes [ 28 , 31 ], but without formal proof by autophagy markers.…”
Section: Resultsmentioning
confidence: 99%
“…9,12,13 This process can also be activated by physiologic stimuli, including Na þ -glucose cotransport. 12,14 In this issue of Gastroenterology, Kaji et al 15 asked if LPA-induced NHE3 exocytosis required MYO5B or, alternatively, be EDITORIALS exploited to stimulate delivery of apical transporters to the brush border in MVID.…”
mentioning
confidence: 99%
“…Defective MYO5B function in microvillous inclusion disease (MVID) leads to loss of brush border transporters as well as essential microvillous structural components (center). Kaji et al15 show lysophosphatidic acid (LPA) can activate a MYO5B-independent exocytic pathway that partially restores brush border transporter expression and microvillous structure (right). engender optimism.…”
mentioning
confidence: 99%